PENGARUH APLIKASI, PEMAHAMAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN MEMBAYAR PBB - Eka Septia Rahmawati; Amin Sadiqin; Abdul Hamid; Taufik Kurniawan (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Land and Building Tax (PBB) is a local tax administered by the regional government. The aftermath of the Covid-19 pandemic has resulted in a downturn in the community's economy, impacting laws and regulations that restrict direct interactions and subsequently affecting tax revenue. To address these challenges, digital technology has been employed. This study aims to investigate the impact of tax application (X1), understanding of taxation (X2), and tax sanctions (X3) on tax compliance (Y). Applying attribution theory and utilizing quantitative research methods, primary data were collected through a questionnaire and analyzed using SPSS 26.00. The findings reveal that tax applications (X1) and understanding of taxation (X2) individually influence compliance with PBB payments (Y), as do tax sanctions (X3). Additionally, collectively, X1, X2, and X3 exhibit a simultaneous effect on variable Y